Tunable metamaterial filter for optical communication in the terahertz frequency range - Yang, Wei; Lin, Yu-Sheng (Optics express, 2020)
We present a design of a tunable terahertz (THz) filter (TTF) used in an indoor communication system. The unit cell of TTF is composed of ring-shaped and cross-shaped nanostructures. By utilizing the micro-electro-mechanical system (MEMS) technique to modify the height between the ring-shaped and cross-shaped nanostructures in the incident transverse electric (TE) mode, the resonant frequencies can be tuned from 0.530 THz to 0.760 THz, which covers an atmospheric window from 0.625 THz to 0.725 THz for indoor wireless optical communication applications. This design of TTF provides an effective approach to select and filter specific signals. It makes the data processing more flexible at the transmission end of the communication system. Furthermore, such a TTF design can be realized the commercialization of communication system components due to its integrated circuit (IC) process compatibility, miniaturization and high flexibility.